2021
DOI: 10.1007/s00127-021-02140-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between common mental disorders (CMDs), food insecurity and domestic violence in pregnant women during the COVID-19 lockdown in Cape Town, South Africa

Abstract: Purpose We aimed to explore the relationship between common mental disorders (CMDs), food insecurity and experiences of domestic violence among pregnant women attending public sector midwife obstetric units and basic antenatal care clinics in Cape Town during the COVID-19 lockdown. Methods Perinatal women, attending 14 healthcare facilities in Cape Town, were enrolled in the study during baseline data collection before the COVID-19 lockdown. During the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 40 publications
(55 reference statements)
0
24
0
Order By: Relevance
“…In children, FI has been associated with decreased academic performance, decreased emotional and intellectual development, delayed development of motor skills, poor general health, iron deficiency anaemia [13], underweight and obesity [1] and stunting [14]. In adults, it has been associated with diabetes, hypertension [15,16], anxiety, depression and suicide ideation [17,18] and other negative health outcomes [16,19], including intimate partner violence perpetration [20,21]. In Africa, a systematic review by Trudell et al [22] found that FI was associated with poor mental health, depending on specific characteristics of study population.…”
Section: Introductionmentioning
confidence: 99%
“…In children, FI has been associated with decreased academic performance, decreased emotional and intellectual development, delayed development of motor skills, poor general health, iron deficiency anaemia [13], underweight and obesity [1] and stunting [14]. In adults, it has been associated with diabetes, hypertension [15,16], anxiety, depression and suicide ideation [17,18] and other negative health outcomes [16,19], including intimate partner violence perpetration [20,21]. In Africa, a systematic review by Trudell et al [22] found that FI was associated with poor mental health, depending on specific characteristics of study population.…”
Section: Introductionmentioning
confidence: 99%
“…The current study also showed that the likelihood of PNDS experienced by unemployed women was 2.7 times higher than that for employed women. Not surprisingly, unemployment is associated with food insecurity, domestic violence, and depression in pregnant and postpartum women [58,59]. Research has further suggested that poverty is a powerful predictor of depression and, as such, disproportionately affects low-income women [60].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous research studies have shown that people with disabilities have lower incomes and are at a heightened risk of food insecurity compared to people without disabilities (Banks et al, 2020 ; Park, Kim, Kim, Jeoung, & Park, 2020 ; The Lancet, 2020 ). Lockdown was especially difficult for already vulnerable groups (Abrahams, Boisits, Schneider, Prince, & Lund, 2021 ); some of the adult patients reported that they had limited access to food and others lived alone without familial support. The non-governmental organisation arranged food parcels for these patients and placed them on their database for follow-up visits.…”
Section: Findings and Discussionmentioning
confidence: 99%